Understanding User Acceptance of Electronic Medical Records: A Mixed method Study - Ekorini Listiowati; Dewanto Dika Pratama; Yuyun Pramayanti; Mohammad Agus Samsudin; Merita Arini; Nurcholid Umam Kurniawan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The advancement of information and communication technology has transformed healthcare delivery into digital systems, notably through the use of Electronic Medical Records (EMRs). The implementation of EMR faces challenges, such as limited human resources, technology adaptation, and slow recording processes. This study aims to evaluate users' acceptance of EMRs and to explore the supporting and inhibiting factors affecting their implementation in a private teaching hospital in Yogyakarta. Methods: A mixed method study with a parallel convergent approach using a cross-sectional (quantitative) and descriptive exploratory (qualitative) design. The quantitative sample was determined by proportionate stratified random sampling. The survey was conducted using a questionnaire based on the Technology Acceptance Model. Qualitative informants were determined purposively and focus group discussions and in-depth interviews were conducted. Quantitative data processing used IBM SPSS version 20 and SmartPLS, while qualitative data processing used thematic analysis, then integrated to obtain a comprehensive understanding. Results: Perceived usefulness scored very good (85%), perceived ease of use was categorized as good (82%), and behavioral intention to use was also good (84%). Structural modeling showed that perceived usefulness and ease of use significantly influenced behavioral intention (p = 0.000; R² = 0.538). Qualitative findings reinforced these results, highlighting key benefits such as improved data accessibility and work efficiency. However, implementation challenges included system security, ethical concerns, and document legality. Conclusion: This study offers methodological, contextual, and conceptual novelty by emphasizing a user-driven adoption process of EMRs. Users actively influenced system design and functionality, rather than relying solely on managerial or vendor decisions. Despite challenges, EMRs have reduced administrative burdens, enhanced operational efficiency, and strengthened clinical documentation. Continuous improvement should prioritize usability, legal compliance, and responsive technical support to optimize the benefits of EMR systems.